The need for reflezxivity in public administration - Cunliffe, Ann L.; Jun, Jong S. (2005)
In this article, the authors argue the need to go beyond the idea of reflective public administration to reflexive public administration. They explore the meaning of reflexity in particular self and critical reflexivity, and suggest that reflexive practice is crucial to public administration because it can lead to more critical, responsible, and ethical actions. This can provide a basis for organizational transformation. The article concludes by offering a number of resources for teaching self- and critical reflexivity. - Reproduced.
Keywords: Public administration